Theorem Details
-- Prove that from P ∨ Q and ¬P, we can conclude Q
theorem disj_elim (P Q : Prop) : (P ∨ Q) → (¬P) → Q := by sorry
Bounty: 0.002 ETH
Status: Closed
Proof
-- Prove that from P ∨ Q and ¬P, we can conclude Q theorem disj_elim (P Q : Prop) : (P ∨ Q) → (¬P) → Q := by intros hPQ hNotP cases hPQ with | inl hP => -- Case where P is true exfalso -- Derive a contradiction apply hNotP -- Use the assumption ¬P exact hP -- Contradicts hP : P | inr hQ => -- Case where Q is true exact hQ -- We can directly conclude Q